2018
DOI: 10.1038/s41598-018-31663-4
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural fungicides inadvertently influence the fitness of Colorado potato beetles, Leptinotarsa decemlineata, and their susceptibility to insecticides

Abstract: The Colorado potato beetle (CPB), Leptinotarsa decemlineata (Say), is an agricultural pest of solanaceous crops which has developed insecticide resistance at an alarming rate. Up to this point, little consideration has been given to unintended, or inadvertent effects that non-insecticide xenobiotics may have on insecticide susceptibility in L. decemlineata. Fungicides, such as chlorothalonil and boscalid, are often used to control fungal pathogens in potato fields and are applied at regular intervals when L. d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…21,22 Because the populations tested here were naive with respect to the tested insecticides, we suspect that regional variation in sensitivity is due to differences in metabolic, excretion, and exclusion mechanisms that may be adaptations to generalized chemical insult resulting from years of exposure to other insecticides or fungicides, and not to target site insensitivities to the tested compounds. 9 The RNA-Seq analysis identified a number of genes coding for detoxification-related products that are constitutively upregulated in the New York population, relative to the Oregon population, supporting the hypothesis that the regional differences in baseline sensitivity may be due to increased expression of genes for generalized metabolism and excretion of toxic chemicals. Population-level differences in the regulation of detoxification genes are correlated with increased tolerance to insecticides in several pest insects, including CPB.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…21,22 Because the populations tested here were naive with respect to the tested insecticides, we suspect that regional variation in sensitivity is due to differences in metabolic, excretion, and exclusion mechanisms that may be adaptations to generalized chemical insult resulting from years of exposure to other insecticides or fungicides, and not to target site insensitivities to the tested compounds. 9 The RNA-Seq analysis identified a number of genes coding for detoxification-related products that are constitutively upregulated in the New York population, relative to the Oregon population, supporting the hypothesis that the regional differences in baseline sensitivity may be due to increased expression of genes for generalized metabolism and excretion of toxic chemicals. Population-level differences in the regulation of detoxification genes are correlated with increased tolerance to insecticides in several pest insects, including CPB.…”
Section: Discussionmentioning
confidence: 67%
“…6,8 Because the potato agroecosystems in the Great Lakes region and East differ in several important respects from those of the Northwest (but not whether or not insecticides are applied), it is likely that CPB populations in those regions may differ in important ways. 9,10 It is not expected, however, that baseline sensitivity of CPB to insecticides with a diverse array of modes of action would systematically differ among these regions, as potato in all of these regions is treated with similar insecticides to control CPB and other insects. 11 Here, we analyzed an aggregate data set of independent bioassay results obtained over 15 years to ask the following question: are there geographic differences in CPB baseline sensitivity to novel insecticides?…”
Section: Introductionmentioning
confidence: 99%
“…While we observed multiple detoxification mechanisms as a response to imidacloprid and chlorothalonil exposure, we did not observe any known detoxification mechanisms as a result of exposure to boscalid. This observation is interesting because it has been previously demonstrated that both chlorothalonil and boscalid can have a driving selection on this insect taxa, including insect mortality at field relevant rates [ 31 ]. More detailed examination of the detoxification mechanisms in common between the imidacloprid and chlorothalonil treatment groups revealed two enzymatic mechanisms of detoxification: a cytochrome p450 ( 6k1 isoform X1) and a UDP- glucuronsyltransferase ( 2b7-like ).…”
Section: Discussionmentioning
confidence: 99%
“…8,40 Similarly, exposure to fungicides have been shown to prime Colorado potato beetles (Leptinotarsa decemlineata) against insecticides through shared activation of detoxification enzymes. 41,42 Most experiments (10 out of 12) in which elevated temperatures were used as an initial stressor, resulted in increased tolerance towards insecticides (Fig. 2).…”
Section: Cross-protection: An Avenue For Tolerance To Multiple Stress...mentioning
confidence: 99%
“…For instance, pre‐exposure to herbicides has been shown to improve survival towards insecticides in the cotton bollworm ( Helicoverpa armigera ) and the tobacco cutworm ( Spodoptera litura ) via the up‐regulation of detoxification genes 8,40 . Similarly, exposure to fungicides have been shown to prime Colorado potato beetles ( Leptinotarsa decemlineata ) against insecticides through shared activation of detoxification enzymes 41,42 …”
Section: Cross‐protection: An Avenue For Tolerance To Multiple Stress...mentioning
confidence: 99%